The mechanism of legal regulation of contractual relations in the conditions of martial law - PRYMAK, Володимир (Ius Modernum, 2023)
At the new stage of Russian armed aggression against Ukraine, the domestic legal system is undergoing large-scale changes associated with the introduction of new legal regulation mechanisms adequate to the current situation, or the adaptation of traditional legal models to existing circumstances. Corresponding legal problems have to be solved in the field of contractual relations – in regulatory and protective legal relations with different subject composition, regarding objects of civil rights that differ in their legal regime. Therefore, the purpose of the presented article is to determine the main parameters of adaptive changes in the mechanism of legal regulation of contractual relations precisely during the period of repelling Russian aggression at the stage of the introduction of martial law in Ukraine. The realization of the set goal involves the application of systemic, formal-legal methods, as well as methods of structural and functional analysis (in particular, the latter are designed to help determine the place, nature of interaction and functional potential of legal means, the totality of which forms the appropriate mechanism). The article emphasizes that, as a component of civil (private) law, contract law in the event of significant threats to the security of the state is decisively influenced by public law, primarily in relation to the limitation of the principle of freedom of contract – in the field of public and defence procurement, ensuring food security, regarding real estate objects. At the same time, any legislative amendments of this kind must be consistent with the principles of justice, reasonableness and good faith. The results of the research made it possible to come to the conclusion that in the conditions of war, all elements of the mechanism of legal regulation of contractual relations are subject to legislative adjustment. These are, among other things, special requirements for the procedure for conclusion, form and content of certain types of contracts as the basis for the emergence and direct regulator of contractual obligations; clarification of the legal status of certain groups of participants in contractual relations and legal regimes of certain types of property; determining the special limits of the application of certain ways of civil legal protection, including the extension of the statute of limitations.